Therapeutic Use of Extraembryonic-Derived Tissues - Michael Uhlin (2735023) (2018)
Instead as being seen as medical waste, umbilical cord blood (UCB), placenta-derived cells, and other extraembryonic tissue are increasingly accepted as a high-quality source of cells for therapeutic use. The best-known application is the transplantation of hematopoietic stem cells (HSCT), while UCB has become an increasingly important graft source since UCB transplantation (UCBT) has been implemented in the last 3 decades. Recently, UCB, placenta, and extraembryonic-derived cells and tissues have been also investigated as a source for adoptive cell therapy. The nonhematopoietic stem cell types in UCB as well as placenta-derived and extraembryonic cells and tissues include several types that can be used therapeutically and are readily expanded to sufficient numbers using established methods. Most notable of these are mesenchymal stromal cells (MSCs) and endothelial-like vascular progenitors (EPCs). To complicate it further, MSCs from different sources of the placenta seem to have very different properties. To even further potentiate the use of extraembryonic-derived tissues for therapy, the sources have to be elaborately characterized. In this special edition, the potential use for this kind of tissues in this was highlighted in several cases illustrating its role in future regenerative medicine. Examples of papers are published in this special edition. Other Information Published in: Stem Cells International License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1155/2018/6082698